Governança e desempenho em cooperativas de crédito - Santos, Marindia Brachak dos (2019)
Corporate governanceis characterized as an innovativesubject forthestrategic management of organizations, and has demanded the attention of several researchers. However, few studies arededicated to unravelingthe intricacies of corporategovernancein the context of cooperativeorganizations. Consideringthat governancepractices often involvediscussions such as theseparation ofownership and management, agencyconflicts betweenrelated parties, theimperfection of contracts and the constant information asymmetry, understandinghow such elements interfereor collaborateto achievegreater performancebecomes essential, especiallyin financial institutions.In this scenario, itisobserved that studies and research in this areahavebeen developingwith greaterintensityin the last decade, even as adeterminingfactor fortheinnovation of processes and risk management of theseinstitutions.However, itis noted thattherearefew studies in the literaturethat evaluate the relationship between governanceandperformancewithin the scopeofthe cooperativecreditsector. Given the above, this studyaimed to analyzethe influenceof governanceon financial performancein creditunionsin Brazil. Regardingthe methodological aspects, the research is characterized as exploratory-descriptivewith quantitative approach and had asampleof 994 creditunionsinstalled in allregions ofBrazil. Theelaboration of the indices that represent the dimensions of supervision and audits (IGOVFIS), strategicdirection (IGOVDIR) and representativenessand participation (IGOVRP) arebased onthe research on governanceapplied byBACEN, in the 2013/2014period. Secondarydata regardingfinancial performancewereobtainedfrom the Central Bankof Brazilbymeasuringfive PEARLSsystem indicators (P1, E1, A2, R5 and L2). Data were processed and analyzedusingtwo analysismethods: multiple linear regression analysis,ordinaryleast squares (OLS), cross-section, and cluster analysis. . Descriptivestatistics show that cooperativeorganizations havemedium and largecharacteristics and arelocated mostlyinthe South and Southeast regions of Brazil. Theempirical evidencefound indicates that theresults are consistent with the theories behind the research. Thus, wehighlight the relevanceofcontract theory, agencytheoryand ownership structurethat, together, allow us to understand and discuss the nuancesthat permeate the complexityof governancein creditunions. Theresults of the fiveestimated models allow us to conclude that corporate governanceinfluencesfinancial performanceincreditunions,however,the level of corporate governancein theseinstitutionsisstill low.Regardinggovernancetypologies, two clusters areformed in theorganizations studied, which differfrom eachother, and in relation to the region of operationand the typeof cooperative. Given the results, this thesis offers asignificant empiricalcontribution to the field of organizational management byinvestigatingtheaspects ofgovernance and performance in a way that is still little addressed in the literature.